Challenges of Inclusive Education in Yogyakarta City - Hanifa, Zulfa Jihan; Salimi, Moh; Sukarno, Sukarno (Universitas Sebelas Maret, 2025)
Inclusive education is one of the efforts to fulfill the right to education for students with disabilities. However, the implementation of inclusive education still faces several challenges. This study aims to identify the challenges in implementing inclusive education, particularly in the city of Yogyakarta. The research method used in this study is a qualitative method with a case study approach. Data collection techniques include interviews and document studies. The subjects of this research consist of the head of the administrative sub-division and two technical service staff members, selected purposively. Based on the results of the study, it was found that the challenges in implementing inclusive education include discrimination and rejection in the admission of new students, teachers being unprepared to provide educational services for students with disabilities, a lack of facilities and infrastructure, as well as numerous unresolved cases involving students with disabilities due to complex handling bureaucracy. Thus, it can be concluded that the implementation of inclusive education in the city of Yogyakarta still faces several challenges.